2007
DOI: 10.1002/macp.200700051
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization Kinetics of Poly(dimethylsiloxane) Molecular‐Weight Blends—Correlation with Local Chain Order in the Melt?

Abstract: The crystallization of bimodal PDMS molecular‐weight blends consisting of long (115 kda) and short (5.3 kda) chains is investigated using DSC and proton NMR. In agreement with earlier studies, it is found that the pure long‐chain sample crystallizes more rapidly than the short‐chain sample. Furthermore, the rate passes through a maximum for the 60:40 blend. These observations hold true for non‐isothermal cooling at −5 K · min−1 and isothermal crystallization at 203 K (both DSC) as well as at 218 K (NMR). The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 63 publications
2
14
0
Order By: Relevance
“…We take H m = 4.619 kJ/mol and S m = 19.6 J/(K mol) as listed in [84]. These values are in good agreement with a recent NMR study ( H m = 4.54 kJ/mol [85] ) and alternative sources ( S m = 19.1 J/(K mol) [86] ). One finds z H = 3.9 and z S = 4.4 from Eq.…”
Section: Local Reversible Meltingsupporting
confidence: 64%
“…We take H m = 4.619 kJ/mol and S m = 19.6 J/(K mol) as listed in [84]. These values are in good agreement with a recent NMR study ( H m = 4.54 kJ/mol [85] ) and alternative sources ( S m = 19.1 J/(K mol) [86] ). One finds z H = 3.9 and z S = 4.4 from Eq.…”
Section: Local Reversible Meltingsupporting
confidence: 64%
“…1 Bimodal MWD polymers are composed of low-and high-molecular weight ( ) contents. Some researchers [2][3][4][5][6] have prepared bimodal polymer blends in experiments and found that bimodal melts have promoted nucleation rate and processability of the material. In particular, the relationship between property and micro-structure of bimodal polyethylene (PE) has been studied, [7][8][9] and it is believed that the entanglements play an essential role for the outstanding properties of bimodal PE.…”
mentioning
confidence: 99%
“…The characteristic transition temperatures of the single components are listed in Table S1. Table 1 shows that all the blends containing the longer chains such as TA270 or TB270 presented a peak of melting at approximately −40/−50°C (Figures S1 and S2), probably due to the crystallization of long PDMS chains, 49 resulting in a completely amorphous material at room temperature.…”
Section: Resultsmentioning
confidence: 99%